2005
DOI: 10.1007/s11745-005-1443-8
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic acid, but not oleic acid, stimulates β‐oxidation in adipocytes

Abstract: The beneficial roles of dietary fish oil in lowering serum TAG levels in animals and humans have been attributed in part to the high content of two n-3 polyunsaturated very long-chain FA, EPA, and DHA. Recent studies show that EPA induces mitochondrial beta-oxidation in hepatocytes, which might contribute to the systemic lipid-lowering effect. Whether EPA affects FA storage or oxidation in adipocytes is not clear. To investigate this possibility, 3T3-L1 adipocytes incubated with EPA (100 microM) for 24 h were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 41 publications
4
44
0
1
Order By: Relevance
“…29) In addition, recent studies have shown that different types of dietary fat diversely influenced endogenous fatty acid oxidation in adipocytes. [30][31][32] In the present study, MLCT significantly enhanced CPT activity and its mRNA level in comparison with LCT in perirenal adipose tissue (Table 5, Fig. 2).…”
Section: Discussionsupporting
confidence: 63%
“…29) In addition, recent studies have shown that different types of dietary fat diversely influenced endogenous fatty acid oxidation in adipocytes. [30][31][32] In the present study, MLCT significantly enhanced CPT activity and its mRNA level in comparison with LCT in perirenal adipose tissue (Table 5, Fig. 2).…”
Section: Discussionsupporting
confidence: 63%
“…The fatty acid composition of flight muscle membranes and adipose tissue reserves become more similar to that of Corophium volutator while the shorebirds prepare for long-distance migration (Fig.·6). In addition to membrane-related effects, EPA and DHA are also known to trigger mitochondrial and peroxisomal proliferation (Froyland et al, 1997;Jump, 2002a;Jump, 2002b;Totland et al, 2000;Yamazaki et al, 1987), and to increase the activities of key Krebs Cycle and ␤-oxidation enzymes (Froyland et al, 1997;Guo et al, 2005;Jump and Clarke, 1999;Sanz et al, 2000;Yamazaki et al, 1987). This study shows that massive consumption of n-3 PUFA causes a rapid increase in the unsaturation levels of muscle PL and adipose tissue NL.…”
Section: Discussionmentioning
confidence: 59%
“…The theory proposes that membrane composition sets metabolic rate by modulating the molecular activity of integral proteins. It is based on the fact that the functional properties of membrane proteins such as electron transport chain enzymes, ion pumps and other ATPases can be affected by their local lipid environment (Guo et al, 2005;Leaf et al, 2005;Swanson et al, 1989;Turner et al, 2005). In trout, experiments where dietary fatty acids were used to manipulate membrane composition of red muscle have provided mixed results.…”
Section: Fish Muscle and The Membrane Pacemaker Theory Of Metabolismmentioning
confidence: 99%